The locus of sexual selection: moving sexual selection studies into the post‐genomics era. (17th April 2015) - Wilkinson, G. S.; Breden, F.; Mank, J. E.; Ritchie, M. G.; Higginson, A. D.; Radwan, J.; Jaquiery, J.; Salzburger, W.; Arriero, E.; Barribeau, S. M.; Phillips, P. C.; Renn, S. C. P.; et al.
Abstract: Sexual selection drives fundamental evolutionary processes such as trait elaboration and speciation. Despite this importance, there are surprisingly few examples of genes unequivocally responsible for variation in sexually selected phenotypes. This lack of information inhibits our ability to predict phenotypic change due to universal behaviours, such as fighting over mates and mate choice. Here, we discuss reasons for this apparent gap and provide recommendations for how it can be overcome by adopting contemporary genomic methods, exploiting underutilized taxa that may be ideal for detecting the effects of sexual selection and adopting appropriate experimental paradigms. Identifying genes that determine variation in sexually selected traits has the potential to improve theoretical models and reveal whether the genetic changes underlying phenotypic novelty utilize common or unique molecular mechanisms. Such a genomic approach to sexual selection will help answer questions in the evolution of sexually selected phenotypes that were first asked by Darwin and can furthermore serve as a model for the application of genomics in all areas of evolutionary biology.